Ensuring improved service delivery to adult learners through training programmes for facilitators in Abia State, Nigeria (2021)
This paper reports efforts of Abia State government in Nigeria towards promoting mass literacy for adult learners in order to meet EFA (Education for All) goal for which the National Commission for Mass Education (NMEC) was established. The study is predictive that mass education should improve in Abia State in the years to come because of the intervention programmes that had been organised for three consecutive years 2017, 2018 and 2019. During the intervention programmes, the topics of discussion centred around the definition of adult education, adult education and development, who adult learners are, facilitators' work and meeting points between facilitators and learners. Having trained five hundred and thirty-nine (539) facilitators with assistance of three resource persons from the academia, administrators of adult education and experienced facilitators on the field for these years, expectations of the state government are high.